Functional fitness assessment of elite athletes - Malikov, N.; Tyshchenko, V.; Bogdanovska, N.; Savchenko, V.; Moskalenko, N.; Ivanenko, S.; Vaniuk, D.; Orlov, A.; Popov, S. (Journal of Physical Education and Sport, 2021)
Defining functional fitness is important for effective forming of athlete training process in different periods of the annual training plan (macrocycle), as well as for reaching the high level of other types of preparedness (general, specific,technical, tactical andpsychological). Unfortunately, nowadays all existing methodological approaches to the Functional Fitness Assessment Test (FFAT) of athletes of different sports specialization are only based on the limited amount of traditional parameters usage whichdramatically decreases the efficiency of biomedical monitoring system and training process. Consequently, the pressing issue is to develop and practically implement the innovative methods of the Functional Fitness Assessment Express Test corresponding to requirements ofhigh sports performance. The aim of our research is to study the efficiency of the innovative Functional Fitness Assessment Test methodfor specific physical preparation increase of elite athletes in different periods of the macrocycle. The basis and methods: 59 elite athletes of different sports specialization (18-24 years old): 14 female and 14 male volleyball players, 13 basketball players, 12 handball players and 6 female sprinters. Testing of all athletes was conducted within the framework of preparatory periods of the two serial competitions applying the traditional and innovative approach to the functional fitness assessment. The results of the study.The obtained data analysis allowed setting the high level of informativeness and objectivity of the suggested innovative Functional Fitness Assessment Test methodreflected in the quality increase of the specific physical preparedness controlin the preparatory period of the macrocycle. Conclusions. Relative changes of all specific physical preparedness parameters, regardless of sex and sports specialization, registered at the final stage of the shaping experiment, credibly (p<0,05) surpassed the score of relative changes of these scores at the final stage of the stating experiment (among male volleyball players up to 2-12%, among male volleyball players up to 2-20%, among basketball players up to 2-3%, among handball players up to 2-4%, among female sprinters up to 2-6%). The results are recommended for practical implementation into the biomedical monitoring system control of elite athletes.